Legal regulation of the use of artificial intelligence in the provision of medical services in the Republic of Uzbekistan and the Russian Federation - Khujaeva Shirinkhon (The Bioscan, 2024)
This paper examines the legal regulation of the use of artificial intelligence (AI) in medicine in the Republic of Uzbekistan and the Russian Federation. Taking into account the rapid development of technologies and their impact on medical services, the relevance of the topic, a comparative review of the legislation of both countries, as well as practical aspects of the use of AI in the medical field are analyzed. Particular attention is paid to ethical issues related to the use of AI, including the protection of personal data and liability for errors. The results of the study can serve as a basis for the formation of recommendations for improving legal regulation and ensuring the safe use of technologies in healthcare.